ANALYSIS OF LEGAL PROTECTION OF LAND OWNERSHIP RIGHTS IN OVERLAPPING CERTIFICATES DUE TO LAND MAFIA ACTIVITIES IN PAGEDANGAN SUBDISTRICT BASED ON STUDY OF DECISION NUMBER 471/Pid/2020/PT.DKI - Gunawan Widjaja (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study discusses the analysis of legal protection of land ownership rights in the context of overlapping certificates caused by land mafia activities in Pagedangan Subdistrict, with a study of Decision Number 471/Pid/2020/PT.DKI. The phenomenon of overlapping certificates is a crucial problem that threatens legal certainty and justice for legitimate land owners, exacerbated by the practice of land mafia illegally manipulating the land administration system. Through qualitative juridical methods and analysis of court decisions, this study reveals how the implementation and effectiveness of legal protection still face significant challenges, including weak supervision and collusion among officials. In addition, this study highlights the role of land mafia in creating double certificates and the resulting social, economic, and legal impacts, as well as the legal implications of the decision as an effort to enforce criminal law. The results of this study provide strategic recommendations to strengthen the land administration system and law enforcement, as well as the need to empower the community so that land ownership rights are optimally protected.